Perkembangan Diatom Perifiton Pada Substrat Buatan di Perairan Pulau Panjang, Jepara - Syauqina Nashihi Aufar; Agus Sabdono; Diah Permata Wijayanti; Munasik Munasik (Universitas Diponegoro, 2023)
Degradation of marine waters in Panjang Island is increasing resulting in high production of benthic periphyton. Procurement of hard substrate as material for artificial reefs is one of the efforts to see the succession pattern of benthic periphyton microscopically. The purpose of this study was to determine the differences in the abundance and composition of diatoms in geopolymer concrete and ordinary concrete substrates. The method used is the field experimental method, immersing different concrete substrates, namely geopolymer concrete (BA) and ordinary concrete (BT) in the sea waters of Panjang Island at a depth of 3 m for 2 months. Periphyton growth on the substrate was observed microscopically using the Scanning Electronic Microscope (SEM) method. Observations were made at immersion time of 1 day (T1), 7 days (T2), 14 days (T3), 28 days (T4), and 56 days (T5). The results showed that there were differences in the development of Periphyton Diatoms between geopolymer (BA) and ordinary concrete (BT) substrates. On both substrates, periphyton growth was found starting from the observation of soaking for 1 day. The density and diversity of periphyton on the BA substrate was higher than that of the BT substrate, with a density of 2535 cell cm-2 and 73 cell cm-2, respectively, and the diversity of H'Shanon Wiener was 4.07 and 0.33. The benefit of this research is to determine the initial succession of biofilm formation on artificial substrates as a building material for artificial reefs for coral reef restoration programs, especially in marginal reef conditions. Degradasi perairan laut di Pulau Panjang semakin meningkat mengakibatkan produksi perifiton bentik yang tinggi. Pengadaan substrat keras sebagai bahan terumbu buatan menjadi salah satu upaya untuk melihat pola suksesi perifiton bentik secara mikroskopis. Tujuan dilakukannya penelitian ini untuk mengetahui perbedaan kelimpahan dan komposisi diatom pada substrat beton geopolimer dan beton biasa. Metode yang digunakan yaitu metode eksperimental lapangan, dilakukan perendaman substrat beton yang berbeda yaitu beton geopolymer (BA) dan beton biasa (BT) di perairan laut pulau Panjangdi pada kedalaman 3 m selama 2 bulan. Pertumbuhan perifiton pada substrat diamati secara mikroskopis menggunakan metode Scanning Electronic Microscope (SEM). Pengamatan dilakukan pada lama perendaman 1 hari (T1), 7hari (T2), 14 hari (T3), 28 hari (T4), dan 56 hari (T5). Hasil penelitian menunjukkan ada perbedaan Perkembangan Diatom Perifiton antara substrat geopolymer (BA) dan beton biasa (BT). Pada ke dua substrat dijumpai pertumbuhan perifiton mulai pengamatan perendaman selama 1 hari. Densitas dan keragaman perifiton pada substrat BA lebih tinggi daripada substrat BT yaitu masing-masing dengan densitas 2535 sel cm-2 dan 73 sel cm-2, dan keragaman H’Shanon Wiener sebesar 4,07 dan 0,33. Manfaat dari penelitian ini adalah untuk mengetahui suksesi awal pembentukan biofilm pada substrat buatan sebagai bahan penyusun terumbu buatan untuk program restorasi terumbu karang khususnya pada kondisi terumbu marginal.